The Correlation Pattern of Learning Style and Teaching Method of Senior High School Students in Jakarta - Franky Franky; Thomas Budiman (Soegijapranata Catholic University, 2021)
As a source of the learning process, a teacher is expected to understand and be aware of the learning style of their students. Every student has a unique learning style. Some students prefer to auditory style, other students prefer to visual style, and another student may prefer the kinesthetic style. These are a few teaching styles, sensing– feeling (people-oriented), sensing–thinking (outcome-oriented), intuitive–feeling (intellectually oriented), and intuitive–thinking (innovation-oriented). This study aims to evaluate the correlation pattern between students’ learning styles and several teaching styles. The sample of this study is 133 senior high school students in Jakarta. The method used in this study is correspondence analysis. The result of this study shows that students with auditory type suit to the intuitive–thinking method and students with visual type suit to sense–the feeling method. Meanwhile, students with kinesthetic type have not suitable for any teaching method if the analysis is conducted by using correspondence analysis. Nevertheless, observation of the mean of the teaching method score has shown that it suits to the intuitive–feeling method